School Absenteeism Among Immigrant and Refugee K-12 Students in Canada: A Scoping Review - Aktas, Tuba (Université d'Ottawa | University of Ottawa, 2025)
School attendance problems (SAPs) are a growing concern among K-12 students in Canada and have serious long-term consequences. Immigrant and refugee students face additional challenges that may increase their risk of absenteeism. However, research on this topic remains limited. This scoping review aimed to map and synthesize the existing research in Canadian literature among immigrant and refugee K-12 students in Canada, with objectives to explore the nature and quantity of the studies, examine how SAPs have been conceptualized and measured, and finally, identify knowledge and research gaps. Following the PRISMA-ScR guidelines, a comprehensive search was conducted across major databases and using snowballing techniques. Thirty-two studies published between 2003 and 2024 met the inclusion criteria. Findings revealed that school dropout and exclusion were the most frequent and explicit SAP-related themes, while other SAP types (school refusal, school withdrawal and truancy) were rarely addressed explicitly. SAPs were secondary findings in the majority of the studies and were often not conceptualized or labeled; instead, descriptions of the students’ SAP experiences were presented in study findings. Although beyond the parameters of this review, findings also signal that exclusionary practices may be a primary and pervasive experience for many immigrant and refugee students. The findings highlight the need for more research that explicitly examines different SAP types within this population to understand both their prevalence and the lived experiences associated with them, including differences across generational immigration status.
Keywords: Absenteeism; Attendance; K-12 students; Immigrant; Refugee; SAPs